ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENGGELAPAN (STUDI KASUS PUTUSAN NO.47/PID.B/2018/PN.MDN) - ROBERTO MANIK; INDRA PURNANTO SIHITE; DAVID YULIANTO TAMBUNAN; WILLIAM HARVERY SIANIPAR (LP2MTBM MAKARIOZ, 2020)
A criminal offense is an act related to trust and property. Criminal offence is governed in the second book of chapters XXIVchapters 372, 373, 374, 375, 376, and 377 PENAL code. Evasion with all kinds of forms is a type of criminal act that is heavyenough to be seen from the consequences it has caused directly to the Pemberantasannya efforts that are heavy enough tobe done. Pemberantasannya criminal acts must be prosecuted in the appropriate manner contained within the criminalCODE, as well as to be involved with the potential of the government and the law enforcement authorities. Law enforcementofficers are elements that carry out their duties accordingly as subsystems of the criminal justice system. Law enforcementofficials have different roles according to their field. The criminal offense that is a crime that is very common and can occur inall areas even the culprit in various layers of society, either the bottom layer until the top layer or can do this criminal offense.The problem raised in the writing of this research is about whether the cause of criminal offence crimes, how to applycriminal provisions against criminal offense based on verdict No. 47/Pid. B/2018/PN. MDN, how legal consideration by thejudge in dropping criminal sanctions against the perpetrator on verdict number 47/Pid. B/2018/PN.Mdn. In this researchstudy the method used is normative juridical research which is research where the author uses only secondary data, namelya data obtained from the literature, books, papers, and legislation relating to criminal acts of darkening. That is the factor ofthe cause of criminal offense on CV. Inti Surya distributions are: The mentality of an Unstrong employee, the fulfillment factorof life and the consumptive lifestyle, the intention and opportunity as well as the nature of human beings, the system ofaccountability and lack of the attitude of the leadership. The provisions of the law in the book to II of the KUHP Chapter XXIVarticle 372 which is a criminal offense of evasion. Consideration of judges before dropping the ruling in the ruling No. 47/Pid.B/2018/PN.Mdn. According to the author's saving is in accordance with the prevailing laws and regulations as presented bythe previous authors, namely based on at least two legitimate evidence tools, in which case the author researched, theevidence used by the judge is a description of the defendant and the accused.